2014
DOI: 10.1177/1745691613513470
|View full text |Cite
|
Sign up to set email alerts
|

Priming, Replication, and the Hardest Science

Abstract: Concerns have been raised recently about the replicability of behavioral priming effects, and calls have been issued to identify priming methodologies with effects that can be obtained in any context and with any population. I argue that such expectations are misguided and inconsistent with evolutionary understandings of the brain as a computational organ. Rather, we should expect priming effects to be highly sensitive to variations in experimental features and subject populations. Such variation does not make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
267
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(276 citation statements)
references
References 51 publications
8
267
0
1
Order By: Relevance
“…If the results change with the variant then that variant is likely the cause. There is an increasing call for the use of experimental methods in studying human behaviour [32][33][34]. However, there are challenges in using experimental methods given the complexity and difficulty of conducting experiments in field settings, where it is harder to control conditions.…”
Section: (B) Experimental Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…If the results change with the variant then that variant is likely the cause. There is an increasing call for the use of experimental methods in studying human behaviour [32][33][34]. However, there are challenges in using experimental methods given the complexity and difficulty of conducting experiments in field settings, where it is harder to control conditions.…”
Section: (B) Experimental Studiesmentioning
confidence: 99%
“…Ongoing resistance to experimental methods is due to beliefs that experiments-especially laboratory based experiments-lack realism, generalizability and replicability compared with traditional methods, such as demographic surveys and naturalistic observations [32][33][34]. However, concerns regarding low realism in experimental methods-particularly in laboratory-based experiments-may be outweighed by the benefits of being able to isolate causal effects, and control variation, allowing for the manipulation of environments in a way that is hard to duplicate in naturalistic settings [32].…”
Section: (B) Experimental Studiesmentioning
confidence: 99%
“…Research shows that views on mass politics emerge from mechanisms designed to manage small-scale social interaction (Petersen, 2012), and differences in political ideology have been shown to relate to basic differences in how individuals understand and approach the social world (Alford, Funk, & Hibbing, 2005;Duckitt & Sibley, 2010;Hibbing, Smith & Alford, 2013, 2014Jost, Federico, & Napier, 2009;Oxley et al, 2008). 2 In particular, research has demonstrated a clear link between conservative ideology and perceived level of between-group conflict.…”
Section: Mechanisms For Assessing Problem-context: the Role Of Politimentioning
confidence: 99%
“…For instance, Doyen and colleagues (Doyen et al, 2012) were unable to replicate the elderly priming effect of Bargh and colleagues (Bargh et al, 1996), and another study (Harris et al, 2013) reported failure to replicate findings of automatic activation of high-performance goals also in the priming paradigm (see Bargh et al, 2001). Although this has generated an ongoing debate (e.g., Cesario, 2014), it nevertheless casts additional doubt on the automaticity vs. control dissociation in cognitive processing.…”
Section: Main Issuesmentioning
confidence: 99%